1996
DOI: 10.1046/j.1471-4159.1996.66020549.x
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid‐Induced Neurite Retraction in PC12 Cells: Neurite‐Protective Effects of Cyclic AMP Signaling

Abstract: Effects of the cyclic AMP second messenger system were studied on the retraction of neurites elicited by the phospholipid mediator lysophosphatidic acid (LPA) in PC12 cells. LPA stimulation inhibited adenylyl cyclase, indicating that the LPA receptor couples to the heterotrimeric G, proteins. However, pertussis toxin or expression of dominant negative Ras did not prevent neurite retraction. In contrast, cholera toxin, forskolin, and application of dibutyryl-cyclic AMP prevented neurite retraction. The neurite-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
80
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(84 citation statements)
references
References 10 publications
4
80
0
Order By: Relevance
“…LPA-induced actin polymerization results in process retraction and cell rounding in neuronal cells such as N1E-115, or stress fiber formation in fibroblast cells (Ridley and Hall, 1992;Jalink et al, 1993). These cellular responses are mediated by actomyosin interactions through activation of the Rho pathway, produc- ing contractile forces that induce cell shape changes (Jalink et al, 1994;Tigyi et al, 1996;Kozma et al, 1997;Hirose et al, 1998;Kranenburg et al, 1999;Fukushima et al, 2000;Weiner et al, 2001). Herein, we have also shown that Rho is activated by LPA in TR cells and LPA-induced process retraction is blocked by a ROCK inhibitor or CD, which indicates the possible involvement of Rho and actomyosin for process retraction in TR cells (Figure 10).…”
Section: Lpa Induces Both Actin Depolymerization and Polymerization Wmentioning
confidence: 64%
“…LPA-induced actin polymerization results in process retraction and cell rounding in neuronal cells such as N1E-115, or stress fiber formation in fibroblast cells (Ridley and Hall, 1992;Jalink et al, 1993). These cellular responses are mediated by actomyosin interactions through activation of the Rho pathway, produc- ing contractile forces that induce cell shape changes (Jalink et al, 1994;Tigyi et al, 1996;Kozma et al, 1997;Hirose et al, 1998;Kranenburg et al, 1999;Fukushima et al, 2000;Weiner et al, 2001). Herein, we have also shown that Rho is activated by LPA in TR cells and LPA-induced process retraction is blocked by a ROCK inhibitor or CD, which indicates the possible involvement of Rho and actomyosin for process retraction in TR cells (Figure 10).…”
Section: Lpa Induces Both Actin Depolymerization and Polymerization Wmentioning
confidence: 64%
“…LPA stimulation of Ga 12 V Radhika et al stimulate Ga 13 or any other a-subunits in a different cellular or physiological context. Results from different laboratories, including ours, indicate that the stimulation of a specific Ga-subunit by LPA is dependent on the cell-type or as well as the physiological context, presumably determined by the type of LPAR expressed (Tigyi et al, 1996). While LPA readily activates Ga 12 in NIH3T3 cells, it has little or no effect on Ga 13 .…”
mentioning
confidence: 58%
“…A role for pertussis toxin (PTX)-sensitive Ga i has been recently proposed in LPA-stimulated cell proliferation (Tigyi et al, 1996). However, the pretreatment of Ga 12 WT-NIH3T3 or pcDNA3-NIH3T3 cells with 15 U of PTX failed to inhibit LPA-stimulated proliferation of these cells (number of cells in Figure 2 LPA stimulates Ga 12 in NIH3T3 cells.…”
mentioning
confidence: 97%
See 2 more Smart Citations